Exploring Exploring Language Attitudes Among Students Across Diverse Geographic Region: A Comparative Study : Exploring Language Attitudes - Muh. Hasby Assidiq; Farisha Andi Baso; Ismail Sangkala; Bahrur Rahman Hasba (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study explores students’ language attitudes toward Indonesian, regional languages, and English across diverse geographical regions in South Sulawesi. Language attitude plays a crucial role in shaping language use, identity, and learning outcomes, particularly in multilingual societies. This research aims to examine how geographical background influences students’ perceptions, preferences, and language practices within academic and social contexts. The study employed a qualitative descriptive research design. Data were collected through semi-structured interviews with fourteen third-semester students of the English Education Department at Universitas Muhammadiyah Makassar, originating from several regions, including Bone, Bulukumba, Sinjai, Jeneponto, Takalar, Gowa, and Pangkep. The data were analyzed using qualitative data analysis procedures involving data reduction, data display, and conclusion drawing. The findings reveal that students demonstrate highly positive attitudes toward the Indonesian language, perceiving it as a unifying national language that facilitates communication across regions and functions effectively in formal and academic settings. Regional languages are strongly valued as symbols of cultural identity and heritage; however, their use is largely restricted to informal domains. English is regarded as an important global language with strong instrumental value for academic achievement and future careers. Despite this recognition, many students experience anxiety and lack confidence when speaking English, particularly in formal situations. Additionally, code-switching emerges as a common communicative strategy, reflecting students’ linguistic flexibility in navigating multilingual environments. Overall, the study concludes that students maintain a balanced multilingual attitude shaped by geographical background, social context, and communicative needs. These findings highlight the importance of inclusive language education policies that support national unity, cultural preservation, and global competence simultaneously.